The Tomato SlVIPP1 Gene Is Required for Plant Survival Through the Proper Development of Chloroplast Thylakoid Membrane - Micol-Ponce, Rosa; García-Alcázar, Manuel; Capel, Carmen; Yuste-Lisbona, Fernando Juan; Pineda, Benito; Atarés, Alejandro; García-Sogo, Begoña; Capel, Juan; Moreno, Vicente; Lozano, Rafael (Frontiers in Plant Science, 2020)
Since membranes play essential roles in all living beings, all cells have developed mechanisms for efficient and fast repair of membrane damage. In Escherichia coli, the Phage shock stress A (PspA) protein is involved in the maintenance of the integrity of its inner membrane in response to the damage produced by exposure to stress conditions. A role in thylakoid membrane maintenance and reorganization has been proposed for VESICLE INDUCING PROTEIN IN PLASTID 1 (VIPP1), the putative PspA ortholog in Arabidopsis thaliana. While some membranes of plant cells have been extensively studied, the biosynthesis and maintenance of chloroplast thylakoid membrane remains poorly known. Here, we report the cloning and functional characterization of the tomato (Solanum lycopersicum L.) ortholog of Escherichia coli PspA and Arabidopsis thaliana VIPP1, which we dubbed SlVIPP1. Our genetic and molecular characterization of slvipp1, an insertional mutant, allowed us to conclude that the tomato SlVIPP1 gene is needed for development, as Arabidopsis VIPP1, but not Escherichia coli PspA. Homozygous slvipp1 tomato plants are albino, and exhibit early lethality and highly aberrant chloroplast development with almost complete absence of thylakoids. The phenotype of tomato RNAi lines and that of additional slvipp1 alleles generated by CRISPR/Cas9 gene editing technology confirmed that the morphological and histological aberrations shown by slvipp1 homozygotes are caused by VIPP1 lack of function. We also found that tomato SlVIPP1 overexpression does not cause any visible effect on plant morphology and viability. Our work with slvipp1 plants evidences that SlVIPP1 is an essential gene required for tomato survival, since its function is crucial for the proper formation and/or maintenance of thylakoid membranes.